The Effect of Inflation Volatility on Household Consumption Expenditure in Emerging Economies - Ragantara Zubaidi; Logan Charbonneau (Economics Note, 2026)
This study examines the effect of inflation volatility on household consumption expenditure in emerging economies. It focuses on price instability rather than inflation levels. The analysis uses balanced panel data from selected emerging economies in Asia, Africa, and Latin America over the period 2000 to 2023. Inflation volatility is estimated using a GARCH(1,1) model to capture time-varying uncertainty in price dynamics. The empirical model applies fixed effects panel regression with robust standard errors to control for unobserved country characteristics and heteroskedasticity. The results show a clear and statistically significant negative relationship between inflation volatility and household consumption expenditure. Higher price instability reduces household spending by increasing uncertainty about future real income. This effect remains robust after controlling for real income, exchange rate volatility, and financial inclusion. The findings support uncertainty-based consumption theory and precautionary saving behavior. Financial inclusion weakens the negative impact of inflation volatility, indicating that access to financial services helps households smooth consumption under macroeconomic shocks. The study contributes to the literature by providing cross-country evidence that isolates the role of inflation volatility in shaping consumption behavior. The results highlight that inflation stability matters beyond average inflation control. Policy implications suggest that monetary authorities in emerging economies should prioritize reducing inflation volatility while expanding financial inclusion to protect household welfare and sustain aggregate demand.